Studi in silico : Hubungan Kuantitatif Struktur-Aktivitas Antivirus SARS-COV2 Pada Senyawa Turunan N-4-benzoil-N’-(4-fluorofenil) tiourea - Anindi Lupita Nasyanka; Diah Ratnasari; Janatun Na’imah; Dini Kesuma (Journal Syifa Sciences and Clinical Research, 2022)
Specific therapies for the SARS-CoV2 virus are still being developed in several countries countries in the world. One of the suspected molecular targets specific to SARS COV2 is the 3CLpro or main protease of the COVID-19 virus. Based on the target of this work, there are similarities between the compounds  N-4-benzoyl-N'-(4-fluorophenyl)thiourea derivatives with their inhibitors. This study aims to develop derivative compounds N-4-benzoyl-N'-(4-fluorophenyl)thiourea as a potential drug candidate inhibiting SARS-CoV2 viral protein using the HKSA method in silicon. Based on the results of the analysis, the best equation for the development of anti-virus SARS-CoV2 was Log 1/C = 0.269 Log P2 – 2.776 Log P + 0.221 cMR +3.195 (n= 8; R = 0.949 S= 0.11399; F=12,119;Sig=0,018). The role of the lipophilic and -containing groups steric can increase its activity as an anti-virus SARS-CoV2 In silico on the modification of the derivative.